EFFECTS OF COENZYME Q10 AND VITAMIN E IN LACTATED RINGER'S EGG YOLK EXTENDER ON PRE-FREEZING SEMEN QUALITY OF GAGA CHICKEN - Halimah Amin; Sri Wahjuningsih; Aulia Puspita Anugra Yekti; Nurul Isnaini; Yuli Frita Nuningtyas (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aimed to evaluate the effect of Coenzyme Q10 (CoQ10) and vitamin E supplementation in lactated Ringer's egg yolk (LREY) extender on the pre-freezing semen quality of Gaga chicken. Semen was collected from six mature Gaga roosters using the dorso-abdominal massage method, pooled, and diluted into four treatment extenders arranged in a completely randomized design with ten replications: T0 (LREY extender as control), T1 (LREY + CoQ10 200 µM), T2 (LREY + vitamin E 5 µg/mL), and T3 (LREY + vitamin E 5 µg/mL + CoQ10 200 µM). The variables evaluated were sperm motility, viability, abnormality, plasma membrane integrity, and DNA damage before freezing. Fresh Gaga chicken semen showed favorable baseline quality, with motility of 88.67 ± 0.22%, viability of 94.54 ± 0.27%, and plasma membrane integrity of 94.53 ± 0.35%. Before freezing, sperm viability differed significantly among treatments (P < 0.05), with T1, T2, and T3 showing higher values than T0. Meanwhile, sperm motility, abnormality, plasma membrane integrity, and DNA damage were not significantly different among treatments (P > 0.05). The combined treatment showed a favorable numerical pattern, particularly for motility, abnormality, and DNA damage. These results indicate that CoQ10 and vitamin E supplementation can help preserve sperm viability during dilution and the pre-freezing stage.